Pengaruh Retailing Mix terhadap keputusan pembelian dan kepuasan konsumen Carrefour di kota Pekanbaru - frinov feldiko ibhar diko (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
The study was conducted at Carrefour Pekanbaru, Riau. The aim is to find out the direct effect of the Dimension of Retailing Mix namely Store atmosphere, store location, product diversity, price, promotion and service on purchasing decisions and customer satisfaction. The study took a sample of 180 consumers. The variables used are Store atmosphere, store location, product diversity, price, promotion and service on purchasing decisions and customer satisfaction. Data were analyzed using SEM (Structural Equation Modeling) analysis which is operated through the Smart PLS 3.2.7 program The results showed that there was an influence of product diversity, price and service on purchasing decisions and customer satisfaction. while Store atmosphere, store location and promotion do not influence purchasing decisions and customer satisfaction. and there is an influence between purchasing decision variables on customer satisfaction, the better the consumer purchasing decisions will increase customer satisfaction.